Visual Analysis of Colorectal Cancer Immunotherapy: A Bibliometric Analysis From 2012 to 2021 - Ma, Long; Ma, Jixiang; Teng, Muzhou; Li, Yumin (Frontiers in Immunology, 2022)
An increasing number of studies have shown that immunotherapy serves a significant role in treating colorectal cancer (CRC) and has become a hotspot. However, few studies used the bibliometric method to analyze this field comprehensively. This study collected 1,899 records of CRC immunotherapy from 2012 to October 31, 2021, and used CiteSpace to analyze regions, institutions, journals, authors, and keywords to predict the latest trends in CRC immunotherapy research. The United States and China, contributing more than 60% of publications, were the main drivers in this field. Sun Yat-sen University was the most active institution, while the National Cancer Institute had the highest frequency of citations. Most publications were published in the Journal for Immunotherapy of Cancer. Adam E Snook was the most prolific writer, while Dung T. Le was the most commonly co-cited author. “T cell”, “MMI” and “PD-1blocked” were the most widely studied aspects of CRC immunotherapy. “Immune checkpoint inhibitor”, “combination therapy”, “drug therapy” and “liver metastases” were current research hotspots. “Tumor microenvironment”, “neutrophils”, “tumor-associated macrophages”, and “suppressor cell” have emerged as research hotspots in recent years. “Gut microbiota”, “nanoparticle” and “tumor mutational burden” as recent frontiers of research that should be closely monitored.